A genomic view of the complexity of mammalian proteolytic systems. (1st April 2005) - Puente, X.S.; Sánchez, L.M.; Gutiérrez-Fernández, A.; Velasco, G.; López-Otín, C.
Abstract : Proteolytic enzymes play an essential role in different physiological processes, including development, reproduction and host defence, as well as in numerous pathologies, like inflammatory diseases, neurological disorders or cancer. The completion of the human genome sequence allowed us to determine that more than 2% of all human genes are proteases or protease inhibitors, reflecting the importance of proteolysis in human biology. To understand better the complexity of proteases in human and other model organisms, we have used the available genome sequences of different mammalian organisms, including mouse, rat and chimpanzee, to identify and compare their degradomes, the complete set of protease genes in these species. Surprisingly, the rodent protease complement is more complex when compared with that of primates, mainly due to the expansion of protease families implicated in reproduction and host defence. Similarly, most differences between human and chimpanzee proteases are found in genes implicated in the immune system, which might explain some of the differences between both organisms. We have also found several genes implicated in reproduction, nutrition and the immune system, which are functional in rat, mouse or chimpanzee, but have been inactivated by mutations in the human lineage. These findings suggest that pseudogenization of specific protease genes has been a mechanism contributing to the evolution of the human genome. Finally, we found that proteases implicated in human hereditary diseases, and especially in neurodegenerative disorders, are highly conserved among mammals.